2022
DOI: 10.22146/ijc.72583
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS Based Metabolite Profiling and Antibacterial Activity of Torch Ginger (<i>Etlingera elatior</i>) Flowers Extract

Abstract: Torch ginger (Etlingera elatior) flowers are well known for their antibacterial effects against Staphylococcus aureus, however, the active compounds are still unknown. The purpose of this study was to conduct GC-MS-based metabolite profiling of torch ginger flower and identify compounds correlated with its S. aureus antibacterial activity using Orthogonal Projection to Latent Structure (OPLS). Using the well diffusion method, the antibacterial activity of ethanol extract, hexane, chloroform, and ethyl acetate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Until now, there has been no research that has identified the volatile compound content of oil palm flowers at different times, in the morning, afternoon and evening. GC-MS is a powerful instrument for identifying volatile compounds from plants [7][8][9]. This study aims to identify the content of volatile compounds in male and female flowers of oil palm based on differences in that time with the GC-MS.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Until now, there has been no research that has identified the volatile compound content of oil palm flowers at different times, in the morning, afternoon and evening. GC-MS is a powerful instrument for identifying volatile compounds from plants [7][8][9]. This study aims to identify the content of volatile compounds in male and female flowers of oil palm based on differences in that time with the GC-MS.…”
Section: ■ Introductionmentioning
confidence: 99%